2020
DOI: 10.3389/fnins.2020.00297
|View full text |Cite
|
Sign up to set email alerts
|

Improved Resting-State Functional Dynamics in Post-stroke Depressive Patients After Shugan Jieyu Capsule Treatment

Abstract: Shugan Jieyu Capsule (SG), a Chinese herbal medicine mainly composed of Acanthopanax and Hypericum perforatum, has been used to ameliorate cognitive impairments and emotional problems induced by post-stroke depression (PSD), while the altered brain dynamics underlying the ameliorative effects of SG have remained unclear. Our study focused on investigating the potential neurobiological mechanisms of SG in improving the cognitive function of PSD patients via restingstate functional magnetic resonance imaging (fM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 35 publications
(35 reference statements)
3
24
0
Order By: Relevance
“…MicroRNA (miR) is a multifunctional endogenous non-coding small molecule RNA, consisting of 18–25 nucleotide sequences and an incomplete 3′-untranslated region of the target mRNA molecule complementary combination. The miRs regulate gene expression and protein synthesis at the post-transcriptional level and participate in cell proliferation, differentiation, apoptosis, and other life activities ( Yao et al, 2020 ). Emerging studies have shown that various miRs, such as miR-21, miR-124, miR-146a, and miR-132, play key roles in neurological disorders and may be feasible therapeutic targets ( Gascon et al, 2014 ; Devaux et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNA (miR) is a multifunctional endogenous non-coding small molecule RNA, consisting of 18–25 nucleotide sequences and an incomplete 3′-untranslated region of the target mRNA molecule complementary combination. The miRs regulate gene expression and protein synthesis at the post-transcriptional level and participate in cell proliferation, differentiation, apoptosis, and other life activities ( Yao et al, 2020 ). Emerging studies have shown that various miRs, such as miR-21, miR-124, miR-146a, and miR-132, play key roles in neurological disorders and may be feasible therapeutic targets ( Gascon et al, 2014 ; Devaux et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The correlation coefficient was converted to z-values using Fisher’s r-to-z transformation, to improve normality. Dynamic functional connectivity (dFC) was calculated using a sliding-window method [ 19 ]; here, the sliding window size was set as 50 TRs (100 s) and sliding step size as 5 TRs (10 s), in line with previous studies [ 20 , 21 , 22 , 23 , 24 ]. For the time series in each window, the dFC matrix was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has suggested that the window length is a critical parameter to acquire dynamic spontaneous brain activity ( Li et al, 2018 ; Cui et al, 2019 ), in which too short a window length might not allow for sufficient estimation of dynamic changes, and too long a window length may not be sufficiently sensitive to detect dynamic activity ( Zhang et al, 2019a ). Therefore, to calculate the dALFF of each participant, we applied 50 TR (125 s) as a moderate sliding window length and 5 TR (10 s) as the step size ( Li et al, 2018 ; Cui et al, 2019 ; Yao et al, 2020 ). The post-processed 202 volume of each participant was divided into 31 windows, and the ALFF map was computed within each window.…”
Section: Methodsmentioning
confidence: 99%